Regulation of AMP-activated protein kinase by natural and synthetic activators - David Grahame Hardie (Elsevier, 2016)
The AMP-activated protein kinase (AMPK) is a sensor of cellular energy status that is almost universally expressed in eukaryotic cells. While it appears to have evolved in single-celled eukaryotes to regulate energy balance in a cell-autonomous manner, during the evolution of multicellular animals its role has become adapted so that it also regulates energy balance at the whole body level, by responding to hormones that act primarily on the hypothalamus. AMPK monitors energy balance at the cellular level by sensing the ratios of AMP/ATP and ADP/ATP, and recent structural analyses of the AMPK heterotrimer that have provided insight into the complex mechanisms for these effects will be discussed. Given the central importance of energy balance in diseases that are major causes of morbidity or death in humans, such as type 2 diabetes, cancer and inflammatory disorders, there has been a major drive to develop pharmacological activators of AMPK. Many such activators have been described, and the various mechanisms by which these activate AMPK will be discussed. A particularly large class of AMPK activators are natural products of plants derived from traditional herbal medicines. While the mechanism by which most of these activate AMPK has not yet been addressed, I will argue that many of them may be defensive compounds produced by plants to deter infection by pathogens or grazing by insects or herbivores, and that many of them will turn out to be inhibitors of mitochondrial function.